Disease predisposition of human leukocyte antigen class II genes influences the gut microbiota composition in patients with primary biliary cholangitis - Huang, Chun-Yang; Zhang, Hai-Ping; Han, Wei-Jia; Zhao, Dan-Tong; Liao, Hui-Yu; Ma, Yin-Xue; Xu, Bin; Li, Li-Juan; Han, Ying; Liu, Xiu-Hong; Wang, Qi; Lou, Jin-Li; et al. (Frontiers in Immunology, 2022)
Background: HLA susceptibility gene is the main genetic risk factor for Primary Biliary Cholangitis (PBC), the prognosis of the disease is linked to gut microbiota dysbiosis. However, it remains unknown whether the HLA alleles are associated to the distribution of gut microbiota and disease severity. Methods: A cohort of 964 Chinese patients with PBC was enrolled in Beijing YouAn Hospital, Beijing, China. High-resolution genotyping of HLA class Ι and class Ⅱ loci was performed by sequence-based polymerase chain reaction on 151 of 964 patients. Stool samples were collected from 43 of 151 fully HLA typed patients to analyze microbiota composition by 16S RNA gene sequencing. Results: Among 964 PBC patients the ratio of male to female (114:850) was 1:7.46, 342 of 964 (35.5%) patients had already developed liver cirrhosis when they were enrolled. PBC patients showed a significantly higher frequency of HLA DRB1*08:03 (21.2% vs. 9.0%, P=0.0001). HLA-DRB1*03:01, DRB1*07:01, DRB1*14:05 and DRB1*14:54 frequencies were also increased but did not reach significance after Bonferroni’s correction. While, the frequency of DQB1*03:01 was significantly lower in PBC (24.5% vs. 39.2%, P=0.0010). Gut microbiota was analyzed from four different perspectives. In Group FHRAC (combination of five high frequency of HLA DRB1 alleles) the microbial community in the positive patients was significantly lower than that in the negative patients (P<0.05). In top 10 genus, the Lachnospiracea_incertae_sedis in the positive patients were higher than that in the negative patients (P<0.05). LEfSe analysis showed different microbiota in different levels in the negative patients but did not show characteristics in FHRAC positive patients. DQB1*03:01 positive patients were mainly concentrated in Lactobacillaceae at the family level. Further comparison on the patients in FHRAC group with liver cirrhosis versus without liver cirrhosis showed that the abundance of Veillonella and antinomycetaceae in PBC cirrhosis patients with FHRAC was significantly higher than that in PBC patients neither cirrhosis nor FHRAC. Conclusion: HLA class II genes may influence the composition of gut mycobiome in patients with PBC. The differential gut microbiota was expressed at different taxonomic levels. The abundance of some bacteria may increase in PBC cirrhosis patients with HLA predisposition genes (FHRAC).